Students' Mathematical Literacy Ability - Adi Julianto Kusnadi; Iyon Maryono; Yayu Nurhayati Rahayu (UIN Sunan Gunung Djati Bandung, 2022)
Today, learning is growing. Especially in mathematics. Students are expected to not only have the ability to count, but have the ability to apply it in dealing with problems in everyday life. This study aims to analyze students' mathematical literacy skills. This research uses a literature review method which is compiled using library studies, this writing study only recognizes and refers to momentary writing. Thoughts and examination results from the investigations of several investigations that have been carried out, are not discussed in depth in this writing study. The results of the writing study are that mathematical literacy skills are used in dealing with problems in real everyday life. In mathematical literacy, there are four important parts, specifically capturing ideas, dealing with problems, conveying, and implementing systems. These parts can be found in the 21st century capabilities that today everyone hopes to be able to move. This ability can be created by being trained through learning strategies that provide experiences to students. There are many learning strategies or approaches that can facilitate this experience. Further research is needed, given the very fast technological advances, especially mathematical literacy skills have a significant commitment, in fact.